Fabrication and performance of PES/Al composite corrosion-resistant coating based on labyrinth effect structure - Peichen Han; Xinxin Tu; Ling Chen; Ping Du (Materials & Design, 2025)
Organic-inorganic composite coatings have consistently garnered significant attention in corrosion protection research due to their exceptional anti-corrosion capabilities. In this study, a labyrinth-type composite coating was prepared by using the polyethersulfone (PES) as skeleton, combined with aluminum (Al) particles as functional fillers. The effects of varying proportions (0–20 wt%) and varying particle sizes (6–15 μm) of Al additives on coating performance were investigated. The mechanical properties of composite coating were assessed by adhesion strength via cross-cut test, pencil hardness, impact resistance, etc. The coating microstructure was examined through scanning electron microscopy (SEM). The electrochemical impedance spectroscopy (EIS), polarization test, cyclic salt spray testing, and solution immersion experiments in water, acid and alkaline. Experimental results demonstrate that the composite coating effectively filled micro-pores generated during PES film formation, simultaneously satisfying mechanical requirements and significantly enhancing corrosion resistance. The optimal proportion of Al powder for the coating is approximately 5 %. PES-7 could improve the electrochemical impedance by 2–3 orders of magnitude to 4.22 × 108 Ω cm2 after 7 days, which is 162 % of the pure PES [lg(|Z|)], and could still maintain high protective ability after soaking in acidic and alkaline solution for 360 h. Meanwhile, the anti-corrosion mechanism and critical influencing factors of this composite coating have been investigated and elucidated.